2017
DOI: 10.1186/s12882-017-0444-6
|View full text |Cite
|
Sign up to set email alerts
|

Renal function in patients with non-dialysis chronic kidney disease receiving intravenous ferric carboxymaltose: an analysis of the randomized FIND-CKD trial

Abstract: Background: Preclinical studies demonstrate renal proximal tubular injury after administration of some intravenous iron preparations but clinical data on renal effects of intravenous iron are sparse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…In addition, patients not responding to oral therapy are not given intravenous iron. Some experts believe that intravenous iron may reduce or delay the use of ESAs in ND-CKD patients [ 21 , 22 , 23 ]. KDIGO suggested treating ND-CKD patients with intravenous iron if they were still iron deficient after three months of oral therapy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, patients not responding to oral therapy are not given intravenous iron. Some experts believe that intravenous iron may reduce or delay the use of ESAs in ND-CKD patients [ 21 , 22 , 23 ]. KDIGO suggested treating ND-CKD patients with intravenous iron if they were still iron deficient after three months of oral therapy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found iron deficiency in ~98% of the patients and intravenous iron corrected patients’ hemoglogin levels [ 24 ]. It is noteworthy that the FIND-CKD trial has shown that intravenous iron targeting low or high ferritin levels has no adverse events on the CKD progression [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to REVOKE, FIND-CKD demonstrated no difference in the risk of infection, CV events, or kidney toxicity during 1 year of follow-up. 59 When interpreting these conflicting results, r several factors. 69,70 First, neither study was adequately powered to evaluate safety outcomes.…”
Section: Risks Of Iron Supplementation With Elevated Ferritinmentioning
confidence: 99%
“…There is extensive clinical trial evidence supporting the efficacy of IV iron preparations in patients with both non-dialysis-dependent and end-stage CKD [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ] and patients with CHF [ 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ], IBD [ 28 , 111 , 112 , 113 , 114 , 115 , 116 , …”
Section: Clinical Use Of IV Ironmentioning
confidence: 99%